Bacterial Epidemiology of Surgical Site Infections after Open Fractures of the Lower Limb: A Retrospective Cohort Study - Tracie Joyner Youbong; Astrid De Pontfarcy; Maxence Rouyer; Alessio Strazzula; Catherine Chakvetadze; Clara Flateau; Samir Sayegh; Coralie Noel; Aurélia Pitsch; Abdelmalek Abbadi; Sylvain Diamantis (MDPI AG, 2021)
Open lower limb fractures are common injuries, and the occurrence of infectious complications after open fractures is a usual problem. The rate of surgical site infections (SSIs) and the nature and resistance of the germs responsible for SSIs remain poorly described. Our aim was to describe the bacterial epidemiology of SSIs after surgical management of an open lower limb fracture. We conducted a retrospective monocentric cohort study from 1 January 2012 to 31 December 2020 based on the analysis of inpatient records in a non-university hospital of Ile de France region. All patients who underwent surgery for an open lower limb fracture were included. A total of 149 patients were included. In our population, 19 (12.7%) patients developed an SSI. Of these 19 patients, the sample was polymicrobial in 9 (47.4%) patients. In 9 (45%) cases, the samples identified a group 3 enterobacteria, Enterobacter cloacae being the main one in 7 (36.9%) cases. Staphylococci were identified in 11 patients, with Staphylococcus aureus in 9 (47.4%). All Staphylococcus aureus were susceptible to methicillin, and all enterobacteria were susceptible to C3G. Among all SSI, 10 (58.8%) contained at least one germ resistant to amoxicillin/clavulanic acid (AMC). The SSIs rate was 12.7%. The main pathogens identified were Enterobacter cloacae and Staphylococcus aureus. The presence of early SSI caused by group 3 Enterobacteriaceae renders current antibiotic prophylaxis protocols inadequate with AMC in half the cases.